PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL DALAM MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA SISWA KELAS XI DI SMA NEGERI 7 DENPASAR - Riskayanti, Ni Luh Putu; Karsana, I Nengah; Garbha Putra, I Gede (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
The learning of Hindu Religion and Moral Education which has a tendency only leads to memorization efforts and is not based on experience, can cause the knowledge gained to be easily lost from students' memories. So that students will be smart theoretically without any application and practice in life. The purpose of this research is to identify the forms of contextual learning models, the supporting and inhibiting factors, as well as the implications for students and teachers. The theories used are: (1) Constructivism Theory from Jean Piaget and Lev Vygotsky, (2) Humanism Theory from Abraham Maslow, and (3) Stimulus Response Theory from Edward Lee Thorndike. This type of research is qualitative with a phenomenological approach. Data collection uses techniques or methods of observation, interviews, documentation, and literature. The results of the study show (1) there are 3 forms of contextual models, namely, the planning stage, the implementation stage, and the evaluative stage. (2) Supporting factors: student enthusiasm in learning, adequate facilities, teachers who master the material. Inhibiting factors: inadequate teacher preparation, students not interested in following lessons, lack of learning media. (3) Implications for students: growing student character, being able to understand subject matter and being able to implement it in everyday life, increasing critical and creative thinking skills. The implication for Hindu Religious Education Teachers is being able to provide meaningful subject matter because of the process of linking the material to students' lives.